The birthday cookbook - Bleckwehl, Mary Evanson (Mankato, Minnesota : Black Rabbit Books, 2020)
"Teaches readers how to make simple and delicious birthday treats through clear directions and illustrated steps."--
Includes bibliographical references.
108687
Keywords: Cooking. -- Juvenile literature; Entertaining; Birthdays; Cookbooks; Juvenile works